2022
DOI: 10.3389/fpsyg.2022.762701
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Deep Learning-Based Gesture Interactive Robot in the Treatment of Autistic Children Under Music Perception Education

Abstract: The purpose of this study was to apply deep learning to music perception education. Music perception therapy for autistic children using gesture interactive robots based on the concept of educational psychology and deep learning technology is proposed. First, the experimental problems are defined and explained based on the relevant theories of pedagogy. Next, gesture interactive robots and music perception education classrooms are studied based on recurrent neural networks (RNNs). Then, autistic children are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…At this point, it is important to highlight the disparity with regard to the characteristics of the target population: sometimes students with certain psychosocial features, and on other occasions, students enrolled in music subjects. Therefore, we could not define a common reference framework for the target population, which is not the case for other topics related to social robotics in the educational context, such as care for people with autism spectrum disorder, a topic widely addressed in the scientific literature (Woo et al, 2021;Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it is important to highlight the disparity with regard to the characteristics of the target population: sometimes students with certain psychosocial features, and on other occasions, students enrolled in music subjects. Therefore, we could not define a common reference framework for the target population, which is not the case for other topics related to social robotics in the educational context, such as care for people with autism spectrum disorder, a topic widely addressed in the scientific literature (Woo et al, 2021;Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, from a perspective linked to health (music therapy), the utilization of robots provides a variety of possibilities. By way of example, Zhang et al (2022) describe an experience that has to do with musical perception through gestural robotics. More precisely, they deal with a therapy of musical perception for autistic children that uses interactive gesture-controlled robots supported by the concept of educational psychology and deep learning technology.…”
Section: Robotics and Music Applied To Education And Other Fieldsmentioning
confidence: 99%
“…The importance of emphasizing music in times of crisis has more positive than negative effects [10], because even in therapeutic devices showed positive and significant effects with the participation of patients [16] where electroencephalogram signals were used and showed that there are differences between people when perceiving music [23]. The combination of music therapy and virtual reality [25] could be anti-stress because it helps to take the mind off social and family pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Music therapy is part of the interdisciplinary science and art whose difference with music education tends to improve and develop non-musical skills for personal and emotional growth of people with the help of the areas of psychology and pedagogy; music improvisation (technical therapy, free therapy and creative music) were used for special education playing a very important role for the growth of skills [19], this is how it was explored and had experiences in learning with music therapy and role playing where learning experiences were identified (personality to be professional, to be prepared and spontaneous, mutual feedback, theoretical and experiential learning) [20], because the return to classes will give a permanent opportunity to learn and achieve impact results [21] with the construction of the inter personal therapy that contains patterns and guides positive and negative change were achieved [22], deep learning in music therapy is used in treatments with autistic children using interactive robots, where relevant points requested by pedagogy are explained and defined, the study of music therapy with electroencephalogram is done [23].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we could see, that since the years 2000s, machine learning (support vector machine, self-organizing maps, decision trees, naive Bayes) followed by the deep learning [7,8] have been massively deployed in the different branches of chemistry and biochemistry to reproduce and simulate in silico different chemical experiments and to classify different animal models and human diseases based on those reactions into groups (e.g. comparison of the metabolic systems in mouse model vs human being, personalized diagnosis of a disease in a human model).…”
mentioning
confidence: 99%